Education for sustainability: challenges and trends - António Areosa Martins (2006)
There has been increasing recognition of the critical role of education for sustainability (ES). This article addresses the subject of ES through all the levels of formal and non-formal education, including basic education, university, organisations (private and public) and lifelong learning. The challenges and implications of effectively incorporating sustainability concepts and principles through all the levels of the education system are presented and analysed. Examples and suggestions are presented and discussed, taking into account the interactions, needs and objectives of people and society.